2021
DOI: 10.1017/cts.2021.871
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case study of successful translational research: Gazelle Hb variant point-of-care diagnostic device for sickle cell disease

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Quantification of HbA and key Hb variants including HbF and Hb HbA2 are essential for accurate detection of β-Thal. The previous Gazelle system has demonstrated its utility in detecting anemia [23] and hemoglobinopathies including SCD, sickle cell trait, Hemoglobin C disorder, and Hemoglobin E Disorder [15][16][17][18][19][20][21][22]. Here, we report the updated version Gazelle which enables, for the first time, POC detection of β-Thal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of HbA and key Hb variants including HbF and Hb HbA2 are essential for accurate detection of β-Thal. The previous Gazelle system has demonstrated its utility in detecting anemia [23] and hemoglobinopathies including SCD, sickle cell trait, Hemoglobin C disorder, and Hemoglobin E Disorder [15][16][17][18][19][20][21][22]. Here, we report the updated version Gazelle which enables, for the first time, POC detection of β-Thal.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging the WHO recognized Hb electrophoresis test, we developed a paper-based, miniaturized Hb electrophoresis platform, Gazelle TM (Fig. 1) [15][16][17][18][19][20][21][22]. Gazelle has been tested in clinical studies in 4 different countries with more than 700 subjects, and demonstrated capability of identifying major Hb variants including HbA, HbE, HbS, and HbF, in adults as well as in newborns with SCD, sickle cell trait, Hemoglobin C disorder, and Hemoglobin E Disorder [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, before starting large-scale manufacturing, it may be reasonable to use cost-effective prototyping methods (e.g., hot embossing, elastomer casting, and 3D printing) to produce smaller quantities of products for analytical validation, clinical validation, usability, and feasibility studies. 26 How can we increase the adoption of microfluidics in biomedical and clinical research laboratories?…”
Section: Technological Challengesmentioning
confidence: 99%
“… 25 Designing microfluidic technologies for POC applications with low-cost fabrication and ease-of-use as primary design criteria could also reduce the need for infrastructure and expertise, such as high-resolution microscopy. 26 Microfluidic designs should incorporate strategies to improve robustness, reducing the influences from environmental variations in temperature, humidity, pressure, vibration, and light sources during transportation and use. Automation, integration, and online sensing, monitoring, and control strategies could be incorporated, as needed, to reduce the need for manual interventions.…”
Section: How Can We Use Microfluidics To Enable the Next Generation O...mentioning
confidence: 99%
“…This retrospective case study regards one EA program administered by MICHR, a Clinical and Translational Research Award (CTSA) institute funded by the National Institutes of Health (NIH) to advance clinical and translational science. A protocol for translational science case studies was followed to enable cross-case analysis of the barriers and facilitators of translational processes [1,2]. The results demonstrate how health care and research teams at U-M adapted the operations of the EA program in ways that were sustainable, collaborative, equitable, flexible, managed for effective and efficient performance, and proportionate to relevant risks [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%